The Effect of an Aqueous Extract of Teucrium polium on Glutathione Homeostasis In Vitro: A Possible Mechanism of Its Hepatoprotectant Action - Stella Shtukmaster; Predrag Ljubuncic; Arieh Bomzon (Advances in Pharmacological Sciences)
Background. Teucrium polium is used in Arab traditional medicine to treat liver diseases. Glutathione is an important intracellular antioxidant, and intrahepatic glutathione levels are depleted in liver diseases. Hypothesis and Aim. This investigation tested the hypothesis that aqueous extracts of T. polium maintains intracellular glutathione levels by augmenting glutathione peroxidase and glutathione reductase activity in cultured hepatocytes. Methods. The effects of increasing concentrations (0.01–1 mg/mL) of aqueous extract of T. polium were assessed in cultured HepG2 cells following 24 hours incubation on (1) cellular integrity using (a) the Trypan blue exclusion assay, (b) the [di-methylthiazol-2yl]-2,5-diphenyl-tetrazoliumbromide (MTT) assay, and (c) the lactate dehydrogenase (LDH) assay; (2) glutathione redox state; and (3) glutathione peroxidase and glutathione reductase activities using a repeated measures experimental design. Results. At concentrations of 0.375 mg/mL and 0.5 mg/mL, the extract increased the intracellular levels of total and reduced glutathione and had no effect on the intracellular amounts of oxidized glutathione. The extract had no effect on glutathione peroxidase and glutathione reductase activities. Conclusion. These data indicate that the mechanism of the hepatoprotective action of aqueous extracts of T. polium may be, in part, due to augmenting intracellular glutathione levels.